1925 Ind. Acts 498, § 10 - (:unkn) unknown (My University, 1925)
Required a license for sale, delivery, transfer, advertisement, exposure for sale, or possession with intent to sell pistol or revolvers. Violators guilty of a felony, punishable by imprisonment of not less than one nor more than two years.
Keywords: LICENSE - DEALERS